Clinical Review of the Effects of Hominis Placental Pharmacopuncture in the Treatment of Facial Spasm Patients - Jo Na-Young; Kim Jeong-Hyun; Roh Jeong-Du (Korean Pharmacopuncture Institute, 2013)
Objectives: The main purpose of this research is to investigate the effect of treatment with Hominis Placental pharmacopuncture (HPP) for 32 patients with hemifacial spasm. Methods: We treated facial spasm patients with acupuncture and HPP at Sabaek (ST2), Seung-eup (ST1), Gwallyeo (SI18), Chanjuk (BL2), Sajukgong (TE23), Hagwan (ST7), Hyeopgeo (ST6), Jichang (ST4), Wan-gol (SI4) and Yepung (TE17), and we investigated the effect by using Scott's scale. The data were analyzed by using the SPSS/10.0 for windows program with descriptive statistics, the paired t-test, and the Shapiro-Wilk normality test. Results: After treatment, the grade of the spasm's intensity based on Scott's description were decreased significantly. About 72% of the patients felt that the combination treatment had produced excellent results. Conclusion: These data suggested that HPP can be useful for treating facial spasm patients.